A Comparison Between SRSS-IE and SSiS-PSG Scores: Examining Convergent Validity. (March 2015) - Lane, Kathleen Lynne; Oakes, Wendy Peia; Common, Eric Alan; Zorigian, Kris; Brunsting, Nelson C.; Schatschneider, Christopher
We report findings of a validation study comparing two screening tools: the Student Risk Screening Scale–Internalizing and Externalizing (SRSS-IE, an adapted version of the Student Risk Screening Scale) and the Social Skills Improvement System–Performance Screening Guide (SSiS-PSG). Participants included 458 kindergarten through fifth-grade elementary students from one school in a southeastern state. Correlation coefficients indicated statistically significant, inverse relations between SRSS-IE scores (SRSS-IE 12 [total score], SRSS-E7 [subscale score which includes original seven items constituting the SRSS], and SRSS-I5 [subscale scores of the five items to address internalizing behaviors]) and Prosocial Behavior, Motivation to Learn, Reading Skills, and Math Skills subscale scores of the SSiS-PSG. Analysis of receiver operating characteristics (ROC) curves contrasting students with significant difficulty versus adequate progress suggested the SRSS-IE12 is more accurate for detecting Prosocial Behavior (area under the curve [AUC] = .972) and Motivation to Learn (AUC = .904) compared with Math (AUC = .817) and Reading Skills (AUC = .805) as measured by the SSiS-PSG. Educational implications, limitations, and future directions are offered.